Phytochemical investigation of unripe banana (Musa AAB) cv. Nendran and its novel ‘Banana Grits’ - Natakkakath Kaliyathan Raveena; Nagaraja Ingaladal; M.V. Reshma; Ravi S. Lankalapalli (Food Chemistry Advances, 2022)
Novel ‘Banana Grits’ (BG) was prepared from the pulp of unripe banana (Musa AAB) cv. Nendran, and their detailed phytochemical investigation is described. The present work serves as a first report of isolation and identification of glycolipids by exhaustive NMR and HR-ESI-MS analysis from Nendran that include glycolipids viz. monogalactosyldiacylglycerols, digalactosyldiacylglycerols, acyl steryl glycosides, glucocerebrosides, and sterylglycoside. Proximate analysis, estimation of total carotenoid content, and the resistant starch content in BG are also reported. In vitro starch digestion pattern indicated that out of 80% of total starch in BG, 21% is slowly digestible starch (SDS) and 42% is resistant starch (RS). The presence of SDS and RS indicates that they may contribute to gut health and glycaemic control.